Comparative Electrochemistry and Electrochromic Application of Novel Binuclear Double-Decker Rare Earth Metal Phthalocyanines Bearing 4-(hydroxyethyl)phenoxy Moieties - ÖZKAYA, ALİ RIZA; ORMAN, EFE BATURHAN (ELECTROCHEMICAL SOC INC, 2019)
In the present work, novel double-decker samarium(III), europium(III), and ytterbium (III) phthalocyanines (SmPc2, EuPc2, and YbPc2) bearing 4-(hydroxyethyl)phenoxy moieties have been synthesized and their electrochemical redox, spectroelectrochemical, and electrocolorimetric properties of the complexes have been inquired comparatively in two different non-aqueous solution. All complexes were observed to expose a series of usually reversible phthalocyanine ring-based one-electron reduction and oxidation processes. The effect of the size of rare earth metal ion was clearly reflected as the modest shift in half-wave potentials. Enriched electron transfer processes of the complexes and the interaction between the electrochemically generated anionic and cationic species caused distinct spectral and color changes, identified with in-situ spectroelectrochemical and in-situ electrocolorimetric measurements in solution medium. Spectroelectrochemical and electrocolorimetric measurements of the complexes were also performed in the solid state as the Langmuir-Blodgett film on an indium tin oxide glass in order to understand their technological applicability in electrochromic devices as color changing material. Comparative evaluation of these measurements suggested that Langmuir-Blodgett films of SmPc2 and EuPc illustrate highly reversible distinct color change from green to purple with satisfying electrochromic performance for electrochromic device applications. (c) 2019 The Electrochemical Society.
Keywords: MICROWAVE-ASSISTED SYNTHESIS; LANGMUIR-BLODGETT-FILMS; COMPLEXES. SYNTHESIS; SENSING PROPERTIES; SPECTROSCOPY; SPECTROELECTROCHEMISTRY; (NA)PHTHALOCYANINATO; NAPHTHALOCYANINE; SUBSTITUENTS; BEHAVIOR